Fault Revealing Test Oracles, Are We There Yet? Evaluating The Effectiveness Of Automatically Generated Test Oracles On Manually-Written And Automatically Generated Unit Tests - Bento, Daniel Correia (2022)
Tese de mestrado, Engenharia Informática, 2022, Universidade de Lisboa, Faculdade de Ciências